ST-Based Fusion Nuclear Science Facility: Breeding Issues and Challenges of Protecting HTS Magnets. (3rd October 2017) - El-Guebaly, L.; Harb, M.; Davis, A.; Menard, J.; Brown, T.
Abstract: The Fusion Nuclear Science Facility (FNSF) is viewed as an essential element of the US developmental roadmap to fusion energy. The spherical tokamak-based FNSF has been designed through a national collaborative effort led by the Princeton Plasma Physics laboratory. High-temperature superconducting (HTS) magnets are potentially attractive for such applications. Among other aspects, the magnet shielding and tritium breeding assessments represent key elements for achieving the design engineering objectives. Numerous inboard shielding and cooling materials have been examined to select an optimal shield that protects the inboard HTS magnet and in the meanwhile enhances the outboard breeding. The breeding blanket of choice is the dual-cooled lead lithium (DCLL) blanket. Our 3-D neutronics model included all blanket internals in great details along with nine specialized ports for blanket testing, materials testing, plasma heating, and current drive. The inclusion of a thin DCLL blanket on the inboard side was deemed necessary to achieve an overall tritium breeding ratio in excess of unity.